Electrical Characterization of V2O5/POMA Deposited by the Casting Technique - Diniz, M.O.; Cestarolli, D.T.; Bianchi, R.F.; Guerra, E.M. (Journal of Composites and Biodegradable Polymers, 2020)
Conductive polymer derivatives, such as poly-o-methoxyaniline (POMA), have been broadly used in different applications because they present characteristics similar to those of polyaniline. POMA can intercalate into a V2O5 matrix to improve its structural and electrical properties, and thin films of V2O5/POMA can be deposited by different techniques to extend their technological applications after intercalation reactions. Then, V2O5/POMA hybrid material was deposited by casting technique and characterizated for, further, to be ued as component in amperometric ammonia gas sensor. Our results show the influence of the deposition technique on electrical properties. Indeed, the values of parameters such as resistance, interface effects and conductivity slightly change according to the deposition technique being used.